Teachers’ Perception toward the Challenges in Online English Teaching during Covid-19 Pandemic - Hermansyah Hermansyah; Aridah Aridah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
Due to the COVID-19 pandemic and government policy to carry out online learning or study from home in Balikpapan, Indonesia, this study aims to describe the teachers’ perception of the challenges in the implementation of online learning in teaching English subjects in the learning process and the recommendation to overcome the problems. This research is a qualitative descriptive study. Three English teachers volunteered to participate in this research through invitation at SMK Nusantara Balikpapan. The research data collected through in-depth interviews, which were analyzed descriptively by using interactive techniques. The Thematic analysis is done by collecting data, reducing data, presenting data, and drawing conclusions. The results of the data analysis show that three English teachers were not too familiar with online learning at first, so they still have many obstacles in the teaching process by using online applications or platforms. There are several obstacles, such as using applications or platforms as media, teachers' knowledge, time schedule, teacher and students’ motivation, and plagiarism. To run online learning, these obstacles should be overcome.